Blaschke Type Normalization on Light-Like Hypersurfaces - Atindogbé, C. (Журнал математической физики, анализа, геометрии, 2010)
In this paper we construct and study a Blaschke type normalization on the lightlike hypersurface immersions with 1-degenerate second fundamental form. We discuss basic examples and establish fundamental equations for this canonical transversal vector bundle. As an application, we characterize the Ricci at 1-degenerate Blaschke immersions.